New chemical insights using weakly supported voltammetry: ion pairing in the EC2 reduction of 2,6-diphenylpyrylium in acetonitrile. - Barnes, E; Wang, Y; Belding, SR; Compton, R (2012)
Pairing effect: Varying the concentration of support electrolyte in the electrochemical EC(2) reduction of 2,6-diphenylpyrylium reveals the presence of ion pairing between the electroactive species and BF(4)(-). Experiment and theory are shown to be in good agreement only if ion pairing is included in the simulations. This previously unanticipated effect is only observable if voltammetry is performed under conditions of weak support.